2005
DOI: 10.1158/1078-0432.ccr-04-1659
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Farnesyltransferase Inhibitor BMS-214662 Given Weekly in Patients with Solid Tumors

Abstract: Purpose: A phase I trial of BMS-214662, a selective farnesyltransferase inhibitor with significant preclinical antitumor activity in which drug was given as a weekly 1-hour infusion for four of six weeks, was conducted to evaluate the tolerability, pharmacokinetics, and pharmacodynamic effect on farnesyltransferase activity in peripheral blood mononuclear cells. Experimental Design: BMS-214662 was given to 27 patients with solid tumors at10 escalating dose levels (28-220 mg/m 2 ) allowing intrapatient dose esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Some effect against normal LTC-IC is not unexpected as, in clinical trials, myelosuppression has been a recognized but manageable side effect of treatment with BMS-214662. 21,38 These results confirm that BMS-214662 is targeting primitive CML stem/progenitor cells and provide further evidence of selectivity for CML over normal cells.…”
Section: Bms-214662 Induces Apoptosis Of CML Stem Cells 2847supporting
confidence: 66%
“…Some effect against normal LTC-IC is not unexpected as, in clinical trials, myelosuppression has been a recognized but manageable side effect of treatment with BMS-214662. 21,38 These results confirm that BMS-214662 is targeting primitive CML stem/progenitor cells and provide further evidence of selectivity for CML over normal cells.…”
Section: Bms-214662 Induces Apoptosis Of CML Stem Cells 2847supporting
confidence: 66%
“…An additional phase I study exploring weekly dosing demonstrated activity in 5 patients with acute leukemia or high-risk MDS (among 30 patients), including two complete responses (213). Phase I studies exploring weekly 1 h infusions and weekly 24 h infusions in solid tumor patients have also been reported (214,215). The toxicity profiles for the two regimens differed significantly.…”
Section: Clinical Activity Of Bms-214662mentioning
confidence: 99%
“…The predominate DLTs were secondary to BMS-214662 and were either an acute (starting within 24 h of receiving BMS-214662) syndrome of a sudden leukopenia/ neutropenia and elevation in serum transaminases or gastrointestinal toxicity (both acute nausea/vomiting and diarrhea occurring days after drug infusion). These have been the DLTs or commonly observed toxicities in other phase I dose escalation studies of BMS-214662 (3,12,14,16,17). Unlike some of the prior studies, renal insufficiency was not observed.…”
Section: Discussionmentioning
confidence: 69%